Providing solutions to livestock-dependent communities to enhance their resilience to the climate crisis while reducing greenhouse gas emissions - Flintan, Fiona E.; Arango, Jacobo (International Livestock Research Institute, 2022)
A poster summary of the CGIAR's initiative on Livestock and Climate developed by Fiona Flintan and Peter Arango.